Protection of Farmers Copyright Rights in a Cleaning Agreement by Regional Government (Study in Clove Production Centers in North Sulawesi) - Deasy Soeikromo (AIBPM Publisher, 2018)
The protection of clove farmers' rights to clove concession agreement is very important. This is because of the imbalance in making the agreement, where farmers who need money are easily dictated by the buyers (ijon). The debt bondage agreement has allegedly caused many farmers to be trapped in adverse transactions and weakened their economic resilience. This study uses normative juridical methods and surveys in several villages such as Ranomerut, Tincep, Munte, and other clove production centers. The result of the research shows that not yet the maximum protection for civic farmer's rights especially in the bond agreement, there is no special regulation such as local regulation (Perda) which regulate and sanction for the buyer (debtors) that harms the farmer, where the practice is still based on the agreement. Another factor is the weak supervision of local governments (Pemda) and villages against the activities of the bonds so that the peasants become unprotected objects. There is urgent need for supervision by the local government against the practices and agreements of bonds, and firm action against buyers (ijon) that harms the clove business from the farmers. Keywords: agreement, ijon, supervision, loss, clove farmer